To convert the quadratic \( y = 2(x - 5)^2 - 10 \) from vertex form to standard form, we will first expand the equation.
-
Start with the vertex form: \[ y = 2(x - 5)^2 - 10 \]
-
Expand \( (x - 5)^2 \): \[ (x - 5)^2 = x^2 - 10x + 25 \]
-
Substitute this back into the equation: \[ y = 2(x^2 - 10x + 25) - 10 \]
-
Distribute the 2: \[ y = 2x^2 - 20x + 50 - 10 \]
-
Combine like terms: \[ y = 2x^2 - 20x + 40 \]
So the standard form of the quadratic is: \[ y = 2x^2 - 20x + 40 \]
Thus, filling in the required format, we have: \[ y = x^2 + (-20) + 40, \] where the coefficient of \(x^2\) is \(2\).
So if you want the final answer as: \[ y = 2x^2 - 20x + 40 \]